ANALYSIS OF INFLUENCE SERVICE QUALITY TO THE CUSTOMER LOYALTY IN SAVING SIMPEDES WITH CUSTOMER SATISFACTION AS MEDIATED VARIABLE ON BRI UNIT PASAR KLECO - Muhamad Aris Munandar (STIE Atma Bhakti, 2017)
The purpose of this research was to examine the effect of: (1) service quality to the customers loyalty, (2) service quality to thr customers satisfaction and (3) customer satisfaction to the customers loyalty, and (4) service quality to the customers loyalty with service quality as mediated variable. The population in this study were all clients of BRI SimpedesPasar Kleco. The samples used by 180 respondents taken by convenience sampling. Analysis techniques using StructutalEqueation Modeling (SEM) and path analysis with the help of LISREL program. The analysis shows (1) Service quality has a positive effect on customer loyalty BRI Pasar Kleco, (2) Service quality has a positive effect on customer satisfaction BRI Pasar Kleco, and (3) satisfaction has a positive effect on customer loyalty BRI Pasar Kleco and (4) customers satisfaction of a mediation effect service quality on customers loyalty. Keywords: Service quality, satisfactionandloyalty, BRIPasar Kleco.